Potential Readings of Water Turbidity Values Based on Optical Sensors on Fish-Rearing Biofloc Media - Siskandar, Ridwan; Wiyoto, Wiyoto; Santosa, Sesar Husen; Sari, Julie Eka; Darmawangsa, Giri Maruto; Hidayat, Agung Prayudha; Dardanella, Derry; Kusumah, Billi Rifa (Photonics Letters of Poland, 2023)
An optical sensor-based water turbidity value reader has been made with an IR-emitting light source, a red LED, and a laser. The tool is made as a solution for reading water turbidity values that are impermeable to light-intensity disturbances. In principle, each light emitter will always shoot toward the sensor. The position of the transmitter and sensor is right between the flowing water pipes. When the water flows, the sensor will read the hardness value of the water (in analog value). Of course, pipes, sensors, transmitting sources, and electronic devices are protected by a casing that is impermeable to light intensity. The casing can be placed outside the pool to facilitate the process of tool maintenance. The tool was made in the SV-IPB University hardware laboratory and tested in the SV-IPB University fish pond from April 2022 to October 2022. Tests for all emitting light sources were carried out on aqueous media which has a flock of 6 ml/l. The results show that the three transmitter sources have analog readings in the same range, namely 2200 to 2300. However, of the three, the red LED transmitter sources have consistent reading values for three replications. Thus, the red LED light emitting source has good potential to be used as an optical sensor to read the value of water turbidity in biofloc media. This was proven again in measurements using variations in flock values (5 ml/l, 6 ml/l, 12 ml/l, and 17 ml/l), indicating that the higher the flock value, the greater the resistance value, so the output voltage value is higher. small. The output voltage value can be calculated from the analog value measured by the device. Full Text: PDF References S.-K. Kim et al., "Different maturation of gut microbiome in Korean children", Front. Microbiol. 13, 1 (2022) CrossRef S. Configuration, "Production of Marine Shrimp Integrated with Tilapia at High Densities and in a Biofloc System: Choosing the Best Spatial Configuration", fishes, 7, 283 (2022). CrossRef H.-H. Huang et al., "FinBERT: A Large Language Model for Extracting Information from Financial Text", Int. Conf., 1 (2022). CrossRef N. H. Sadi, D. Agustiyani, F. Ali, M. Badjoeri, Triyanto, "Application of Biofloc Technology in Indonesian Eel Anguilla bicolor bicolor Fish Culture: Water Quality Profile", IOP Conf. Ser. Earth Environ. Sci., 1062, 1 (2022). CrossRef M. M. Rashid, A. A. Nayan, M. O. Rahman, S. A. Simi, J. Saha, M. G. Kibria, "IoT based Smart Water Quality Prediction for Biofloc Aquaculture", Int. J. Adv. Comput. Sci. Appl., 12, 56, (2021). CrossRef D. Krummenauer, A. Freitas Silva, M. Xavier, L. H. Poersch, A. Cardozo, "Comparative analysis of the culture of pink shrimp Farfantepenaeus brasiliensis and Pacific white shrimp Litopenaeus vannamei in biofloc system", Aquac. Int., 1 (2022). CrossRef A. Suloma Mahmoud, A. H. Gomaa, M. A. A. Abo-Taleb, H. R. A. Mola, M. S. Khattab, R. S. Mabroke, "Heterotrophic biofloc as a promising system to enhance nutrients waste recycling, dry diet acceptance and intestinal health status of European eel (Anguilla anguilla)", AACL Bioflux, 14, 1021 (2021). DirectLink M. E. Ramadani, B. Raafi’u, M. Mursid, R. H. Ash-Shiddieqy, A. T. Zain, A. Fauzan Ladziimaa, "Design and Development of Monitoring System on Carp Farming Ponds As IoT- Based Water Quality Control", ICRACOS 2021 - 2021 3rd Int. Conf., 5, 148 (2021). CrossRef G. S. Carter, K. P. Kowalski, M. R. Eggleston, "Turbidity and Estimated Phosphorus Retention in a Reconnected Lake Erie Coastal Wetland", Water (Switzerland), 14, 1 (2022). CrossRef I. I. Mohamedd, N. Hikmah, B. Azizan, N. Elfadil, M. Pahang, "Design and Development of Microcontroller Based Automatic Fish Feeder System", Ijesc, 10, 25380 (2020). DirectLink